2015
DOI: 10.1080/10236244.2015.1041240
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and oxidative damage responses in different organs of Pacific white shrimpLitopenaeus vannamei(Boone, 1931) reared in a biofloc technology system

Abstract: Shrimp (Litopenaeus vannamei) reared in a conventional seawater (SW) aquarium system SW were compared with those raised in a biofloc technology (BFT) system. After 30 days, the L. vannamei shrimp were euthanized and samples of gills, hepatopancreas and muscle were dissected. Statistical analysis was performed using bi-factorial ANOVA, with the factors of the treatment (shrimp reared in SW or in a BFT system) and organs (gills, hepatopancreas and muscles). No differences (p > 0.05) in glutathione-S-transferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
(34 reference statements)
2
12
0
Order By: Relevance
“…The PRE and PhRE of P24 + B and P29 + B were higher than those of P34 + B and P34, and the SGR and FCR of P34 were also higher than P34 + B. Some previous studies had also demonstrated similar results that biofloc did not improve the growth performance of cultured animals (Dauda et al, 2018;Kumar et al, 2017;Little et al, 2008;Martins, Flores, Porto, Wasielesky, & Monserrat, 2015;Nootong, Pavasant, & Powtongsook, 2011). Above all, the water quality of high-protein fed tanks was worse than that of low-protein fed tanks in the biofloc-based system Xu, Pan, Zhao, et al, 2012).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…The PRE and PhRE of P24 + B and P29 + B were higher than those of P34 + B and P34, and the SGR and FCR of P34 were also higher than P34 + B. Some previous studies had also demonstrated similar results that biofloc did not improve the growth performance of cultured animals (Dauda et al, 2018;Kumar et al, 2017;Little et al, 2008;Martins, Flores, Porto, Wasielesky, & Monserrat, 2015;Nootong, Pavasant, & Powtongsook, 2011). Above all, the water quality of high-protein fed tanks was worse than that of low-protein fed tanks in the biofloc-based system Xu, Pan, Zhao, et al, 2012).…”
mentioning
confidence: 65%
“…Some previous studies had also demonstrated similar results that biofloc did not improve the growth performance of cultured animals (Dauda et al, 2018;Kumar et al, 2017;Little et al, 2008;Martins, Flores, Porto, Wasielesky, & Monserrat, 2015;Nootong, Pavasant, & Powtongsook, 2011). Some previous studies had also demonstrated similar results that biofloc did not improve the growth performance of cultured animals (Dauda et al, 2018;Kumar et al, 2017;Little et al, 2008;Martins, Flores, Porto, Wasielesky, & Monserrat, 2015;Nootong, Pavasant, & Powtongsook, 2011).…”
mentioning
confidence: 68%
“…Biofloc microbial communities can also affect the antioxidant and oxidative damage responses in shrimp grown in BFT system. For instance, glutathione (GSH) concentration in the gills and hepatopancreas was lower in BFT-raised L. vannamei than in those reared in traditional, seawater system (da Silva Martins et al 2015). Glutathione peroxidase was upregulated only in BFT group; superoxide dismutase (SOD) expression was lower in BFT-reared shrimp than those grown in recirculating system without biofloc (Soto-Alcal a et al 2019).…”
Section: Antioxidant Effectsmentioning
confidence: 99%
“…Based on its composition characteristics, bioflocs should present an antioxidant activity (Ju et al, 2008;Martins et al, 2015) and also stimulate digestive enzyme activities, improving feed utilization and increasing dietary antioxidant assimilation.…”
Section: Resultsmentioning
confidence: 99%
“…The assimilation of nitrogen compounds by heterotrophic bacteria in BFT allows the same water to be used for several production cycles with no negative environmental impact (Krummenauer, 2014). In addition, the BFT system can promote an enhancement in the immune cellular response and antioxidant status of shrimp Martins et al, 2015). The immune and antioxidant systems play an important role in animal physiology and are crucial to control their health and growth performance.…”
Section: Introductionmentioning
confidence: 99%